2011
DOI: 10.1186/1475-9276-10-37
|View full text |Cite
|
Sign up to set email alerts
|

Gender equality in couples and self-rated health - A survey study evaluating measurements of gender equality and its impact on health

Abstract: BackgroundMen and women have different patterns of health. These differences between the sexes present a challenge to the field of public health. The question why women experience more health problems than men despite their longevity has been discussed extensively, with both social and biological theories being offered as plausible explanations. In this article, we focus on how gender equality in a partnership might be associated with the respondents' perceptions of health.MethodsThis study was a cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 31 publications
(33 reference statements)
1
21
0
2
Order By: Relevance
“…Gender relations [6, 28, 33]Refers to how we interact with or are treated by people in the world around us, based on our ascribed or experienced gender.How might the outcomes of implementation interventions differ by sex and gender according to whether the degree to which the geographic setting is culturally homogeneous, diverse or gender equitable?What are the implications of an implementation intervention being communicated or delivered to women only, men only, men and women separately or together? How is this mediated by cultural context?The Self-Perceived and Self-Reported Gender Equality scale [77]. Institutionalized gender [6, 28, 33]Reflects the distribution of power between men and women in the political, educational, and social institutions in society.…”
Section: Discussionmentioning
confidence: 99%
“…Gender relations [6, 28, 33]Refers to how we interact with or are treated by people in the world around us, based on our ascribed or experienced gender.How might the outcomes of implementation interventions differ by sex and gender according to whether the degree to which the geographic setting is culturally homogeneous, diverse or gender equitable?What are the implications of an implementation intervention being communicated or delivered to women only, men only, men and women separately or together? How is this mediated by cultural context?The Self-Perceived and Self-Reported Gender Equality scale [77]. Institutionalized gender [6, 28, 33]Reflects the distribution of power between men and women in the political, educational, and social institutions in society.…”
Section: Discussionmentioning
confidence: 99%
“…In reviewing the literature, a qualitative study conducted in Colombia suggested that household members with chronic conditions can help support and remind each other in performing self‐care behaviours (eg, take medication) (Legido‐Quigley et al, ). Further, perceived family support is essential for the patients to improve adherence to healthy self‐care behaviours (Sörlin, Lindholm, Ng, & Öhman, ). Consistent with the traditional Saudi culture (Alrukban et al, ), we found 86% of respondents reported strong family support.…”
Section: Discussionmentioning
confidence: 99%
“…Gender refers to the socially constructed roles, behaviours, activities, and attributes that a given society considers appropriate for men and women” [ 7 ]. Sweden is regarded as a country with a high level of gender equality in international comparison, and gender equality is an undisputable societal norm [ 8 ]. Still gender continues to play a considerable part in how work, wealth, power, and time use are distributed in the Swedish society [ 9 ].…”
Section: Introductionmentioning
confidence: 99%